Гармонический анализ субструктурных параметров деформированных металлов - Засимчук, Е.Э.; Засимчук, В.И.; Гонтарева, Р.Г.; Турчак, Т.В.; Тарасенко, Л.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The substructure parameters in tension- and rolling-deformed nickel, Al, and Al-alloy are
determined by X-ray diffraction peak proﬁle analysis. It is shown by theoretical calculations
that the Fourier coefficients of proﬁles can be obtained from the experimental curve but not
from the α1-curve proﬁle. The non-monotone change of the substructure parameters during
the deformation process and a drastic decrease of microstresses in blasted tension-deformed
specimens are described. These X-ray data are compared with the TEM information.